The Role of Productive Zakat in the Development of the Halal Industry and Improving the Economy of the Ummah - Abdurrouf (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
The distribution of productive zakat needs to innovate so that it has maximum value in improving people's welfare and synergizes in developing halal industrial areas so that the poor have an important role in the development of halal industrial areas. This conceptual research aims to develop a synergy model for the development of the halal industrial area based on the distribution of productive zakat. The benefits of this paper can be used as a reference for policy-making designs related to the establishment of halal industrial estates, especially on financial support and business actors as well as uses related to poverty alleviation. This research method is conceptual research by analyzing the results of research and reviewing previous literature and conducting exploration at the implementation level. The result is that productive zakat can be used as a driving force for the growth and development of halal industrial estates by establishing joint businesses (syirkah) of mustahiq (zakat recipient groups) accompanied by halal business consultants and making productive zakat recipients both managers and shareholders so that their welfare increases and guaranteed.